Causality of School Libraries and Student Success - Pasquini, Laura A.; Schultz-Jones, Barbara (Qualitative and Quantitative Methods in Libraries, 2019)
Three independent, concurrent meta-syntheses of education policy, theory, and best practices research compiled a corpus of scholarship-related student success, learning, and achievement. These efforts relate to the research question, “To what extent do the causal relationships between school-based factors and student learning offer possible causal relationships between school libraries and student learning?” This empirical literature collection was compiled using a mixed research synthesis approach: a review of “mixed” objects of synthesis as well as the mode of synthesis of research published between 1985-2016. The process and results are detailed.